An investigation of operative outcomes: Pediatric invasive fungal sinusitis. (November 2017) - Hanba, Curtis; Svider, Peter F.; Lai, Wanda; Raza, Syed Naweed; Sheyn, Anthony; Eloy, Jean Anderson; Folbe, Adam J.
Abstract: Objectives/Hypothesis: Invasive fungal sinusitis is an uncommon entity among children. Early recognition is crucial for facilitating successful treatment with minimal morbidity. The goal of this analysis was to identify patient characteristics associated with high-risk surgical disease through a population-based examination into this rare and deadly disease process. Methods: A retrospective chart review of the 2009 and 2012 Kids' Inpatient Database (KID) was conducted. A series of queries (Fungal infection→immunocompromised diagnosis→sinus procedure) identified 102 patients with likely invasive fungal sinusitis. Outcomes included: species, invasive extension, death, and other clinical characteristics. Results: Patients with leukemia/lymphoma constituted 90.2% of individuals evaluated in this analysis. Nearly a quarter of pediatric patients receiving surgical treatment for invasive fungal sinusitis died during their hospital stay –24.9%. Aspergillus was the most commonly recorded mycotic species. Average hospital stay was 59.3 days, and associated hospital costs averaged 746, 299 per stay. Patients 0–5 years old were more likely to have orbital involvement –56.3%. Brain extension was noted in 33.7% of this cohort as well. Mucormycosis was an independent predictor of death (p = 0.03), with an odds ratio of 3.835. Conclusion: To the best of our knowledge, this is the largest pediatric cohort with invasive fungal sinusitis in the literature. Patient demographics, cytology, and disease extension offer predictive information regarding patient outcomes for invasive fungal sinusitis. A high clinical suspicion and early treatment may decrease the lengthy and costly hospitalizations in this population.